Royal jelly production in Africanized colonies with selected queens, use of Chinese model cups and supplementation - Pereira, Heber Luiz; Santos, Pedro da Rosa; Rossoni, Diogo Francisco; Toledo, Vagner de Alencar Arnaut de (Acta Scientiarum. Animal Sciences, 2019)
This research was carried out to evaluate the royal jelly production in two trials. In Trial I, three genotypes of Africanized honeybees (Apis mellifera L.) were submitted to royal jelly production with two types of cups of different size and volume (conventional and Chinese model) and two types of supplements (commercial and formulated). A total of 24 colonies were used, two bars with different cups each, alternating between the upper or lower position of the frame. While in Trial II, 18 colonies, two genotypes, two types of cups and two types of supplement were tested. The evaluated parameters were: percentage of larvae accepted in upper and lower bars, royal jelly per cup (mg), and royal jelly per colony/collection (g). Chinese cups were not well accepted, fact that influenced in a negative way the production of general form, selected colonies were more sensible to the change of cups. Colonies of Africanized honeybees are not prepared to produce in cups of greater volume.